DRILL CUTS CONTAMINATED WITH DIESEL TREATMENTS - Romero Silva, Roberto; Chao Reyes, Claudia; González Suárez, Aimeé; Comesañas García, Yumirka; Barrios San Martín, Yaima; Ameneiros Martínez, José María (Centro Azúcar Journal, 2021)
Introduction: In drilling oil wells process, water or oil-based muds are used. During these activities drag rock fragments detached by drilling bit action, called drilling cuts, towards the surface. These cuts inadequate handling generates an environmental contamination problem. Objective: To evaluate a chemical-biological stabilization process as drilling cuts contaminated with diesel fuel mud treatment, in microcosm, in a 90 days period. Materials and methods: Chemical stabilization stage was carried out by adding calcium oxide (CaO), biological one is a bioremediation process, through soil cultivation technique and a bio stimulation method. In biological stage, two experimental variants were evaluated as sources of nutrients, a soil improver product (V1) and Agromena (V2). For applied treatment evaluation, fats and oils (G and A) biodegradation rates (TB) and total hydrocarbons (HCT) were determined. Results and Discussion: 56% and 44% TB were obtained for 1 and 2 variants, respectively, in terms of G and A; while reached was 72% and 43% for HCT the TB, respectively. Conclusions: Achieved results showed that proposed treatment application is feasible for these residues safe management, reaching the highest degradation levels with soil improver product.